Understanding Environmental Degradation through African Proverbs - Maiwong, Eric Dzeayele (International Journal of Language and Literary Studies, 2025)
This paper investigates the effects of environmental degradation on humanity, linguistics, knowledge, and culture. This study employs a tripartite theoretical framework to analyze L?mnso’ proverbs: Structural Linguistics, Semiology, and Critical Discourse Analysis (CDA). Basing its analysis on thirty-nine L?mnso’ proverbs, the study rigorously demonstrates that the extra-linguistic and sociological variables in the data contribute to the process of signification—or meaning generation—in language at both denotative and connotative levels. The paper reveals that geographical environmental degradation has devastating consequences for humanity, linguistics, knowledge, and culture. It argues that environmental degradation is a long-standing concept in African societies, particularly in the Nso’ community, dating back as far as the Nso’ people, their language (L?mnso’), and their culture. Furthermore, by presenting fresh and reliable evidence, the study establishes that language is intrinsically linked to environment, knowledge, and culture. Its key contributions include: 1. Highlighting a previously neglected aspect of linguistic studies—the relevance of geographical environment to meaning generation and effective communication. 2. Proposing that game reserves and forest reserves should serve not only as touristic sites but also as knowledge-based, linguistic, and cultural laboratories.